2010
DOI: 10.1029/2010ja015361
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step evolution of auroral acceleration at substorm onset

Abstract: [1] The sudden formation of parallel electric fields in the magnetosphere-ionosphere (M-I) coupling system is essential to complete substorm onset. From this standpoint, we focus substorm ignition on field-aligned acceleration by studying the dynamical behavior of auroral kilometric radiation. Field-aligned auroral acceleration shows a distinct two-step evolution at substorm onset: the activation of low-altitude acceleration (h ∼ 4000-5000 km) which corresponds to auroral initial brightening and the subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 101 publications
9
65
0
Order By: Relevance
“…[20] The multistep activations around the auroral breakup (with intervals of several minutes) have been discussed in previous studies [e.g., Kadokura et al, 2002;Morioka et al, 2010;Saito et al, 2010]. They concluded that the stepwise evolution of auroral breakup was likely common.…”
Section: The Westward Expansion On 26 February 2008mentioning
confidence: 99%
“…[20] The multistep activations around the auroral breakup (with intervals of several minutes) have been discussed in previous studies [e.g., Kadokura et al, 2002;Morioka et al, 2010;Saito et al, 2010]. They concluded that the stepwise evolution of auroral breakup was likely common.…”
Section: The Westward Expansion On 26 February 2008mentioning
confidence: 99%
“…In a statistical investigation, Morioka et al [2010] showed that the generation of fieldaligned currents and accelerated auroral electrons in the auroral current circuit is tightly coupled to flow burst in the plasma sheet. Indeed, 65% of the flow bursts observed from Geotail data appeared to correspond to the generation of auroral kilometric radiation (AKR) in the auroral acceleration region within the M-I coupling region [Morioka et al, 2010]. Moreover, recent investigations by Marghitu et al [2010] and O.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the frequency-time spectrogram (f-t diagrams) of AKR observed by GEOTAIL and AL/AU index on 5 December 1995. The arrows in the f-t diagram show the transient AKR with sudden frequency expansion to lower frequencies accompanied with substorm onset [e.g., Anderson et al, 1998;Morioka et al, 2010]. The frequency expansion indicates that the AKR source region extended up to 14,000 km of altitude (see the right-side ordinate).…”
Section: Two Types Of Akrmentioning
confidence: 99%
“…The frequency expansion indicates that the AKR source region extended up to 14,000 km of altitude (see the right-side ordinate). Morioka et al, [2010] showed that this AKR breakup appears at auroral breakup and is composed of two source regions: high-altitude (typically 6000-12,000 km) and lowaltitude (typically 3000-5000 km) AKR sources. This sudden frequency expansion of AKR is termed transient AKR in this paper.…”
Section: Two Types Of Akrmentioning
confidence: 99%
See 1 more Smart Citation